Genetic diversity of East and West African Striga hermonthica populations and virulence effects on a contrasting set of sorghum cultivars. (22nd October 2014) - Bozkurt, M L; Muth, P; Parzies, H K; Haussmann, B I G; Novak, Stephen
Summary The root hemiparasite Striga hermonthica causes very significant yield loss in its dryland staple cereal host, Sorghum bicolor. Striga‐resistant sorghum cultivars could be an important part of integrated S. hermonthica control. For effective resistance breeding, knowledge about the diversity of the parasite is essential. This study aimed (i) to determine the genetic diversity within and between seven S. hermonthica populations from East and West Africa using 15 microsatellite markers and (ii) to assess the virulence and host–parasite interactions of these Striga populations grown on 16 diverse sorghum genotypes in a glasshouse trial. Most of the genetic variance (91%) assessed with microsatellite markers occurred within S. hermonthica populations. Only a small portion (8%) occurred between regions of origin of the populations. A positive correlation (R2 = 0.14) between pairwise geographic and genetic distances reflected the slightly increasing differentiation of S. hermonthica populations with increasing geographic distance. East African S. hermonthica populations, especially those from Sudan, had significantly greater average infestation success across all sorghum genotypes than West African populations. Some specific host–parasite interaction effects were observed. The high genetic variation among individuals of each S. hermonthica population underlines the high potential adaptability to different hosts and changing environments. This points to the need to manage sorghum resistance alleles in space and time and to employ resistant varieties as part of integrated S. hermonthica control, so as to hinder the parasite overcoming resistance.